2017
DOI: 10.1111/jnc.14095
|View full text |Cite
|
Sign up to set email alerts
|

Targeted unlabeled multiple reaction monitoring analysis of cell markers for the study of sample heterogeneity in isolated rat brain cortical microvessels

Abstract: Liquid chromatography coupled to tandem mass spectrometry-based targeted absolute protein quantification (in fmol of the analyte protein per μg of total protein) is employed for the molecular characterization of the blood-brain barrier using isolated brain microvessels. Nevertheless, the heterogeneity of the sample regarding the levels of different cells co-isolated within the microvessels and bovine serum albumin (BSA) contamination (from buffers) are not always evaluated. We developed an unlabeled targeted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Cell markers quantifiable in homogenate were GLUT1, GFAP, aquaporin (AQ)4, neural‐glial antigen (NG)2, SYP, and ß‐integrin (CD11b). Protein concentrations of GLUT1 in BMEC were significantly higher than homogenate indicating brain endothelial cell enrichment ( Figure a ) . The protein concentrations of CD31 and vWF were quantifiable in BMEC but not the corresponding homogenate, further supporting brain endothelial cell enrichment.…”
Section: Resultsmentioning
confidence: 94%
“…Cell markers quantifiable in homogenate were GLUT1, GFAP, aquaporin (AQ)4, neural‐glial antigen (NG)2, SYP, and ß‐integrin (CD11b). Protein concentrations of GLUT1 in BMEC were significantly higher than homogenate indicating brain endothelial cell enrichment ( Figure a ) . The protein concentrations of CD31 and vWF were quantifiable in BMEC but not the corresponding homogenate, further supporting brain endothelial cell enrichment.…”
Section: Resultsmentioning
confidence: 94%
“…These results are comparable to previously reported LC–MS/MS proteomic data on rat brain microvessels (Gomez‐Zepeda et al . ), where 1640 proteins were identified, including 44 SLC and 6 ABC transporters. Although the two studies identified similar numbers of proteins and transporters, the two datasets were rather complementary, where the overlap was 30 SLC and 4 ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Cldn5 is one of the main integral membrane proteins that comprise BBB tight junctions, with the greatest density in the capillaries and smaller venules, and least in the larger venules[ 60 ]. Pecam1 is normally found on endothelial cells and several types of blood cells, and has been used as a marker for the normalization of protein quantification in endothelial cells[ 15 ]. As expected, significantly higher expression of Cldn5 (mean of 36-fold) and Pecam1 (mean of 25-fold) were detected in BrMV (with >50% BrEC) than those in CDB samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the unique structure of the BBB, contamination of BrMV with cells other than BrEC is unavoidable, regardless of isolation methods involving either mechanical[ 12 ], enzymatic[ 13 ] or laser microdissection[ 14 ] techniques. The variations in relative purity or cellular composition among different BrMV isolates may have significant consequences in data interpretation and research outcome, especially for experiments designed for high-throughput genomics and proteomics technologies [ 15 , 16 ]. No standard criteria or systematic method is currently available to evaluate the purity or cellular composition of microvessels, although it can be detected by visual inspection using light microscopy.…”
Section: Introductionmentioning
confidence: 99%